Mid-term Clinical and Radiological Results of Surgically Treated Pediatric Medial Humeral Epicondyle Fractures: Screw or K Wire? - (:unkn) unknown (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2018)
Objective: The aim of the present study was to evaluate the clinical and radiological radiological results of surgically treated pediatric medial humeral epicondyle fractures which were fixed with screw or K wire. Materials and Methods: The study was designed retrospectively. Twenty two patients were evaluated clinically and radiologically. Functional outcomes were assessed with the Mayo elbow performance index (MEPI) and the Turkish Language version of the shortened version of the Disabilities of Arm, Shoulder, and Hand (Quick DASH) scale. Results: All fractures were healed. The mean MEPI was 99.3 points (range, 85-100), with 21 patients as excellent and 1 good results. The mean MEPI was 100 points for patient who was fixed with K wires (group A). Excellent results were obtained for all patients. The mean MEPI was 97.9 points (range, 85-100) for patients with screw fixation (group B). Excellent results were obtained for all patients, except one. The mean Quick DASH score was 0.63 (range, 0-9). It was found 0.33 (range 0-5) and 1.3 (range, 0-9) for group A and group B, respectively. Two (13%) minor complications were developed in group A and 4 (57.3%) in group B. The difference for Quick DASH and MEPI scores were statistically insignificant (p>0.05). Conclusion: Both of fixations with K wire or screw provide enough stability until the fracture healed. Fracture union could be obtained for both fixation type and the clinical and radiological results were similar. The need for secondary operation for implant removal and higher complication rates seems the negative side of screw fixation. Keywords: Medial epicondyle fracture, K wire
Keywords: Medial epicondyle fracture; surgery; screw; K wire; OPERATIVE TREATMENT; CHILDREN; DISPLACEMENT; FIXATION; OUTCOMES